DOI: 10.29007/1hrc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Climate Change on Streamflow in Kon – Ha Thanh River Watershed, Vietnam

Abstract: Climate change is a complex problem and becoming the leading challenge for humankind in the 21st century. It will affect almost aspects of human well-being. Therefore, assessing climate change impacts on water resources and proposed solutions to respond to climate change is urgent and necessary. This study applied the SWAT model (Soil and Water Assessment Tool) and GIS (Geographic Information System) technique to simulate water flows due to the impact of climate change. The models were applied for Kon -Ha Than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…In recent years, this well-known watershed-scale model has been used more frequently in the United States, Europe, and other regions [70] due to its high capability to solve hydrological-related issues. Many studies have used SWAT to reveal the impacts of land-use and land cover (LULC), climate change [71], robustness of SPPs [13], and pesticide and agricultural chemical pollutions on streamflow or sediment loads [5,13,48,70,[72][73][74][75][76]. The first version of this model was developed for ArcGIS, as explained by [69,76].…”
Section: Swat Modelmentioning
confidence: 99%
“…In recent years, this well-known watershed-scale model has been used more frequently in the United States, Europe, and other regions [70] due to its high capability to solve hydrological-related issues. Many studies have used SWAT to reveal the impacts of land-use and land cover (LULC), climate change [71], robustness of SPPs [13], and pesticide and agricultural chemical pollutions on streamflow or sediment loads [5,13,48,70,[72][73][74][75][76]. The first version of this model was developed for ArcGIS, as explained by [69,76].…”
Section: Swat Modelmentioning
confidence: 99%
“…Furthermore, the understanding of urbanization development and its effects on regional temperature during thermal-extreme events is especially critical for coastal regions [40]. This scientific basis is also valuable for streamflow assessment within the context of climate change [41,42]. However, several recent study attempts regarding this topic by [7,25,38,39] for the north midlatitude area of Vietnam (Hanoi city) could not help in this case, in which the chosen study area is the low-land coastal region, Central Vietnam.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have highlighted the effects of climate change on the natural water cycle (Bolch et al, 2012;Aryal et al, 2019;Bhatta et al, 2019;Roderick et al, 2019;Tran et al, 2023b). Floods caused by extreme rainfall are expected to become more frequent across the globe (Chattopadhyay et al, 2017;Vo et al, 2018;Ivanov et al, 2021;Tran et al, 2023b), and are likely to persist even more severely in the near future. Besides, Lehner et al (2019) observed that the flow patterns of a third of the world's 200 largest rivers have changed since the 1950s, with these alterations being directly attributable to climate change.…”
mentioning
confidence: 99%
“…Although it is challenging to obtain an accurate prediction of streamflow under the climate impacts, it remains a crucial undertaking for effective water resource planning, regional management, and mitigation of extreme events (Khoi and Suetsugi, 2012;Tran et al, 2022c;Tran et al, 2022e;Umar et al, 2022). In Vietnam, a number of studies have investigated the impacts of climate change at various scales (Khoi and Suetsugi, 2012;Ty et al, 2012;Huyen et al, 2017;Vo et al, 2018;Giang and Vy, 2021). However, the majority of these studies were carried out in previous decades with the neglect of important factors (e.g., man-made infrastructures), raising concerns about their reliability which is relevant to the current specifics of climate change in this region.…”
mentioning
confidence: 99%
See 1 more Smart Citation